KINERJA KARYAWAN DALAM PENANGANAN DOKUMEN EKSPOR FREIGHT FORWARDING - A.J Muljadi; Khansa Khairunnisa; Lira Agusinta (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
This study was conducted to find out the effect of employees’ performance in handling export documents to the effectiveness of goods delivery.  PT Iron Bird Transport is a private company focuses on domestic and international delivery and logistics. The company thinks that employees’ performance is important to achieve the satisfaction from customers. There are 30 employees in operational export division as survey respondents. This study was using simple linear regression analysis and coefficient correlation method. From the data processing can be seen that there is a significant effect on human resources performance in managing export documents to the effectiveness of goods delivery based on the results of hypothesis : tcount > ttable or 5,836 > 1,697.